Evaluation of Some Hematological and Biochemical Parameters in Mature Female Domestic Cats (Himalayan) at Different Reproductive State - Mohammed Abdulsalam (Basrah Journal of Veterinary Research)
The present study was conducted at College of Veterinary Medicine– University of Basrah. Ten adult's mature female domestic cats (Himalayan) and five mature males were used in the study to investigated the reference value of some hematological and biochemical parameters at different reproductive status. The cats divided into five periods non-pregnant, pregnant at first, second and third trimester and after parturition (lactation) period, the cat housed in special room in a hotel for cats in Basra city. The results showed non-pregnant cats exhibited normal value of hematological parameters like red blood cell, hemoglobin concentration, packed cell volume. Mean corpuscular volume, and mean corpuscular hemoglobin concentration, while red blood cell, hemoglobin concentration, packed cell volume showed significantly decreased with advanced period of gestation and lactation. white blood cell showed increased significantly in late gestation and lactation periods, serum level of liver enzymes ALT increased in lactation period and ALP increased in third trimester and lactation period. Lipid profile like total cholesterol and triglyceride showed increased significantly in third trimester and lactation periods, urea and creatinine appeared increased in third trimester only. It is concluded that some of blood and biochemical parameters are exchange with advanced period of gestation and lactation period.